Biocrust reduces the soil erodibility of coral calcareous sand by regulating microbial community and extracellular polymeric substances on tropical coral island, South China Sea - Wang, Lin; Huang, Yu; Yang, Qingsong; Mai, Zhimao; Xie, Feiyang; Lyu, Lina; Zhang, Si; Li, Jie (Frontiers in Microbiology, 2023)
Tropical coral islands assume a pivotal role in the conservation of oceanic ecosystem biodiversity. However, their distinctive environmental attributes and limited vegetation render them highly susceptible to soil erosion. The biological soil crust (biocrust), owing to its significant ecological role in soil stabilization and erosion prevention, is deemed an effective means of mitigating soil erosion on coral island. However, existing research on the mechanisms through which biocrusts resist soil erosion has predominantly concentrated on arid and semi-arid regions. Consequently, this study will specifically delve into elucidating the erosion-resistant mechanisms of biocrusts in tropical coral island environments, South China Sea. Specifically, we collected 16 samples of biocrusts and bare soil from Meiji Island. High-throughput amplicon sequencing was executed to analyze the microbial community, including bacteria, fungi, and archaea. Additionally, quantitative PCR was utilized to assess the abundance of the bacterial 16S rRNA, fungal ITS, archaeal 16S rRNA, and cyanobacterial 16S rRNA genes within these samples. Physicochemical measurements and assessments of extracellular polymeric substances (EPSs) were conducted to characterize the soil properties. The study reported a significantly decreased soil erodibility factor after biocrust formation. Compared to bare soil, soil erodibility factor decreased from 0.280 to 0.190 t h MJ−1 mm−1 in the biocrusts. Mechanistically, we measured the microbial EPS contents and revealed a negative correlation between EPS and soil erodibility factor. Consistent with increased EPS, the abundance of bacteria, fungi, archaea, and cyanobacteria were also detected significantly increased with biocrust formation. Correlation analysis detected Cyanobacteria, Chloroflexi, Deinococcota, and Crenarchaeota as potential microbials promoting EPSs and reducing soil erosion. Together, our study presents the evidence that biocrust from tropical coral island in the South China Sea promotes resistance to soil erosion, pinpointing key EPSs-producing microbials against soil erosion. The findings would provide insights for island soil restoration.